Efficiency analysis of an isolated high voltage gain converter operating in resonant and non-resonant mode - Spiazzi, Giorgio; Sichirollo, Francesco; Goncalves, Flavio A. S. [UNESP] (Institute of Electrical and Electronics Engineers (IEEE), 2012)
This paper presents an efficiency investigation of an isolated high step-up ratio dc-dc converter aimed to be used for energy processing from low-voltage high-current energy sources, like batteries, photovoltaic modules or fuel-cells. The considered converter consists of an interleaved active clamp flyback topology combined with a voltage multiplier at the transformer secondary side capable of two different operating modes, i.e. resonant and non-resonant according to the design of the output capacitors. The main goal of this paper is to compare these two operating modes from the component losses point of view with the aim of maximize the overall converter efficiency. The approach is based on losses prediction using steady-state theoretical models (designed in Mathcad environment), taking into account both conduction and switching losses. The models are compared with steady-state simulations and experimental results considering different operating modes to validate the approach. © 2012 IEEE.
Keywords: Active clamp; Converter efficiency; Efficiency analysis; Energy processing; Energy source; Flyback; High voltage gain; High-current; Low-voltage; MathCAD; Nonresonant; Operating modes; Output capacitor; Photovoltaic modules; Steady-state simulations; Step-up ratio; Switching loss; Theoretical models; Transformer secondaries; Voltage multipliers; DC-DC converters; Exhibitions; Energy conversion